SOCIO-PHILOSOPHICAL ANALYSIS OF THE IMPACT OF GLOBALIZATION PROCESSES ON LABOR MIGRATION TO UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
This article analyzes the impact of globalization processes on labor migration in the Republic of Uzbekistan from a socio-philosophical point of view. Currently, the Integrative processes taking place in the World, Economic and technological development, changes in the international labor market have a significant impact on the reasons for the exit of citizens of Uzbekistan to labor migration and its consequences. Labor migration is studied not only as an economic phenomenon, but also as a complex process covering social, cultural and philosophical aspects. Research carried out within the framework of the topic analyzes the influence of globalization factors on migration processes on the basis of a systematic approach. In particular, the balance of supply and demand of the international labor market, the development of migration policies, regulatory measures carried out by the state and their effectiveness are discussed. The main areas of labor migrants of Uzbekistan, their impact on society, social adaptation, changes in their economic situation and the role of labor migration in the national development strategy are considered. In addition, in our study, the positive and negative aspects of labor migration are analyzed and issues such as demographic and social problems arising from it, family and cultural changes, knowledge and skill migration are covered. At the same time, advanced strategies and recommendations for improving the migration policy of the state of Uzbekistan are presented. This article is aimed at a deeper understanding of the processes of labor migration of Uzbekistan, which serves to reveal its philosophical and social aspects.